ASSOCIATION BETWEEN SLEEP QUALITY AND GERIATRIC SYNDROMES IN NURSING HOME RESIDENTS - Tuğba Turgut; Remzi Bahşi; Deniz Mut Sürmeli; Hande Selvi Öztorun; Çağlar Coşardereliğoğlu; Volkan Atmış; Ahmet Yalçın; Murat Varlı; Sevgi Aras (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Background: With aging, an increase is observed in some geriatric syndromes as well as sleep disorders. Objective: The aim of this study is to investigate the relationship between sleep quality and geriatric syndromes (dementia, depression, sarcopenia, malnutrition, and frailty) in nursing home residents. Methods: The participants’ demographic characteristics, comorbid diseases, number of drugs, cognitive performance, mood and nutritional states, sarcopenia and fraility screening tests and sleep quality test were evaluated by two geriatricians. The participants were divided into two groups as good sleep quality and poor sleep quality. Correlation analysis of sleep quality and geriatric and mental functionality tests was performed with Spearman correlation analysis. Results: A total of 104 nursing home residents (34 females, 74 males, aged 61-98) participated in the study. Sleep quality was found to be worse in the elderly between the ages of 75-84, with a higher number of children, using assistive devices, and taking selective serotonin reuptake inhibitors. In addition, in participants with poor sleep quality, SARC-f (strength, assistance with walking, rising from a chair, climbing stairs, and falls) and geriatric depression scale scores were significantly higher. The Pittsburgh Sleep Quality Index global score was negatively associated with total sleep time and positively associated with geriatric depression scale score and SARC-f score. Conclusion: Findings from the present study in relation between poor sleep quality and some geriatric evaluation parameters suggests that there may be a common pathophysiological alteration with aging.